The Catch-22 in Israel’s parole law - Assy, Rabeea (Criminal justice and behavior, 2014)
This article reviews the general legal framework governing risk assessment of prisoners in the Israeli parole process. It highlights the excessive power the Israeli courts have accorded to the professional body responsible for providing risk assessments, which severely limits the parole board's discretion to order conditional release when prisoners persist in denying their crimes. Such prisoners, especially sex offenders, tend to be precluded from participation in treatment courses, thus substantially reducing their prospects of obtaining parole.